Detection of Genomic DNA Damage from Radiated Nasopharyngeal Carcinoma Cells Using Surface-Enhanced Raman Spectroscopy (SERS). Issue 11 (November 2016) - Ou, Lin; Chen, Yang; Su, Ying; Zou, Changyan; Chen, Zhong
Structural changes and chemical modifications in DNA during interactions with X-ray radiation are still not clear within 48 h of incubation. We investigate genomic DNA from the radiated CNE2 cell line within 48 h of incubation using surface-enhanced Raman spectroscopy (SERS). Multivariate methods including principal component analysis (PCA) and random forest are proposed to explore the statistical significance before and after radiation. Our results show that intensities of several bands change after radiation, which indicates backbone damage and base-unstacking. Biological effects from DNA damage repairing process may be simultaneously stimulated and different from incubation time. Under doses of 10 Gy (with 24 and 48 h of incubation) and 20 Gy (with 48 h of incubation), the relative contents of C against T and A against G deviate obviously from the control level. Statistical results strengthen significantly the idea that modification in DNA bases is associated with the disruption of base-stacking in the DNA duplex. Our findings provide vital information for radiation-induced the DNA damage at the molecular level, which may provide insight into the effect and mechanism of anticarcinogens in tumor therapy.